Using Artificial Seagrass for Promoting Positive Feedback Mechanisms in Seagrass Restoration - Carus, Jana; Arndt, Carmen; Schröder, Boris; Thom, Moritz; Villanueva, Raúl; Paul, Maike (Frontiers in Marine Science, 2021)
Worldwide, seagrass meadows are under threat. Consequently, there is a strong need for seagrass restoration to guarantee the provision of related ecosystem services such as nutrient cycling, carbon sequestration and habitat provision. Seagrass often grows in vast meadows in which the presence of seagrass itself leads to a reduction of hydrodynamic energy. By modifying the environment, seagrass thus serves as foundation species and ecosystem engineer improving habitat quality for itself and other species as well as positively affecting its own fitness. On the downside, this positive feedback mechanism can render natural recovery of vanished and destroyed seagrass meadows impossible. An innovative approach to promote positive feedback mechanisms in seagrass restoration is to create an artificial seagrass (ASG) that mimics the facilitation function of natural seagrass. ASG could provide a window of opportunity with respect to suitable hydrodynamic and light conditions as well as sediment stabilisation to allow natural seagrass to re-establish. Here, we give an overview of challenges and open questions for the application of ASG to promote seagrass restoration based on experimental studies and restoration trials and we propose a general approach for the design of an ASG produced from biodegradable materials. Considering positive feedback mechanisms is crucial to support restoration attempts. ASG provides promising benefits when habitat conditions are too harsh for seagrass meadows to re-establish themselves.